1994
DOI: 10.1021/jm00048a005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Diuretic Activity of Alkyl- and Arylguanidine Analogs of N,N'-Dicyclohexyl-4-morpholinecarboxamidine in Rats and Dogs

Abstract: Random screening identified N,N'-dicyclohexyl-4-morpholinecarboxamidine (U-18177, 1) as an orally effective nonkaliuretic diuretic in rats. The diuretic profile of 1 and its 1-adamantyl analog (U-37883A, 4) was confirmed orally in dogs, when they were less potent than standard diuretics but showed furosemide-like natriuresis at > or = 100 mumol/kg. However, acute 1 at 61 and 90 mumol/kg iv resulted in lethal cardiac toxicity in dogs. Many analogs of 1 exhibited qualitatively similar diuretic profiles, but none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…2, acute i.v. PNU-18177A unexpectedly reversed minoxidil's arterial hypotension in conscious dogs, suggesting direct antagonism of the latter's peripheral vasodilation (91). A similar vascular interaction was subsequently confirmed with PNU-37883A, which reversed the effects of minoxidil in anesthetized cats (Fig.…”
Section: Chemistry and Initial Detection Of Biological Activitysupporting
confidence: 57%
See 1 more Smart Citation
“…2, acute i.v. PNU-18177A unexpectedly reversed minoxidil's arterial hypotension in conscious dogs, suggesting direct antagonism of the latter's peripheral vasodilation (91). A similar vascular interaction was subsequently confirmed with PNU-37883A, which reversed the effects of minoxidil in anesthetized cats (Fig.…”
Section: Chemistry and Initial Detection Of Biological Activitysupporting
confidence: 57%
“…In conscious rats, PNU-37883A (10 to 100 mg/kg p.o.) increased urinary volume and Na + exertion two-to sixfold without the kaliuresis seen with hydrochlorothiazide and furosemide or the K + retention common to amiloride and triamterene (91). A similar two-to 10-fold eukalemic natriuresis was also seen in conscious dogs with i.v.…”
Section: Diuretic Activity In Rats and Dogsmentioning
confidence: 74%
“…porter, resulting in natriuresis (26)(27)(28). Other compounds that also ostensibly produce natriuresis via inhibition of K+ channels have been described; however, LLU-a is the most potent inhibitor yet reported (29)(30)(31), with an ID50 of about 5 nM.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, therefore, that BTS 67 582 exerts it diuretic activity via inhibition of renal tubular KATP channels. The diuretics ZM181,037 [Kau et al, 1994] and U-37883A [Perricone et al, 1994;Humphrey et al, 1995;Humphrey, 1995] have been reported to cause eukalemic diuresis in dogs broadly similar to that observed with BTS 67 582. Interestingly, ZM181,037 and U-37883A [Wang et al, 1995] inhibit renal tubular KATP channel activity and possess functional antagonism of KATP channels in vascular tissue, but are devoid of glucose-lowering activity.…”
Section: Discussionmentioning
confidence: 82%